2012
DOI: 10.1007/s12217-011-9294-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bond Number on Behaviors of Liquid Drops Deposited onto Solid Substrates

Abstract: The problem of spreading behaviors of pendant and sessile drops was studied experimentally and numerically under the action of gravity force and surface tension. Bond number was considered to be a main factor of the influence on shape behaviors of liquid drops. This study was performed in the framework of an experimental investigation of drop behaviors in microgravity onboard a Chinese satellite in future. The experiments were carried out in the Drop Tower of Beijing, which could supply about 3.6 s of microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
(22 reference statements)
0
25
0
Order By: Relevance
“…The experiments using the Drop Tower of Beijing [23] report a stabilization time from 0.8 to 1.2 seconds in the case of sessile drops, while by the experiments using the Drop Tower Facility of Queensland [22], the vibration time for sessile drops to reach equilibrium is less than 0.5 seconds. These authors carefully observed the transition from formal to reduced gravity using a 30 fps camera.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The experiments using the Drop Tower of Beijing [23] report a stabilization time from 0.8 to 1.2 seconds in the case of sessile drops, while by the experiments using the Drop Tower Facility of Queensland [22], the vibration time for sessile drops to reach equilibrium is less than 0.5 seconds. These authors carefully observed the transition from formal to reduced gravity using a 30 fps camera.…”
Section: Resultsmentioning
confidence: 96%
“…during the release of the capsule to the free fall. Recent experiments realized in 2012 by Diana et al [22] using the Drop Tower Facility of the Queensland University of Technology (Queensland, Australia) and Zhu et al [23] using the Drop Tower of Beijing (National Microgravity Laboratory, Beijing, China) showed that the simple wire cutting release mechanism that initiates the drop of the experimental rack induces vibrations on the drop. According to [22], the sudden variation of the gravity force induces oscillations in the sessile drop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Leger, Joanny, Fujji and Nakae, only forces that become increasingly large at the contact line such as the viscous force on an advancing liquid can affect Young's law. However, recent experimental evidence using microgravity by parabolic arc flights [21] and microgravity drop towers [22][23] have demonstrated that the effect of gravity on the contact angle is relevant even at very small drop volumes such as 5 µL. According to Allen [24], who studied the wetting of very small drops with small contact angles, a drop is small enough to neglect gravitational influences only if its volume is less than 1 µL.…”
Section: Introductionmentioning
confidence: 99%
“…These four distinct categories of wettability phenomenon occur as a result of balance between gravity and surface tension forces. [5] The wettability behaviours on the surface were originally defined by the Wenzel and Cassie-Baxter states. [6][7][8] The Wenzel assumes that the liquid wet the whole rough surface, whereas the Cassie-Baxter assumes that droplet partially wet the rough surface due to trapped air in the microstructures.…”
Section: Introductionmentioning
confidence: 99%